Effects of Non-Stoichiometry on Magnetic Properties and Microstructure of Ni₀.₃Zn₀.₇Fe₂ ±ₓO₄ and Mg₀.₅Zn₀.₅Fe₂ ±ₓO₄ - Alias, Rosidah (2003)
Various non-stoichiometric compositions of Ni-Zn ferrites and Mg-Zn ferrites were investigated. The samples were prepared by the conventional sintering method while being subjected to an air annospheric condition. The measurement of magnetic properties such as magnetic permeability, magnetic loss, Curie temperature, magnetic flux density and microstructure were performed to understand the magnetic properties of samples prepared by systematic compositional changes. X-ray diffraction results indicate that the samples are in good crystalline form. Curie temperature variation can be explained on the basis of Neel's two sub-lattices model and could be due to distribution of magnetic ions between two sub-lattices. The dependence of magnetic permeability with temperature shows that the trends exhibited by all the samples are similar. With increase in temperature, permeability increases gradually and then shows sudden drop at the Curie point because the anisotropy constant decreases more rapidly than the saturation magnetization. The dependence of permeability on iron oxide content obeys globus model. The change of permeability in the cation-deficient region is caused by the positive contribution of the anisotropy constant to the total anisotropy during conversion of Fe3+ ions to Fe2+ ions. However, for the anion-deficient region, the variation in permeability is mainly accounted to be due to microstructural changes. The loss factor and the quality factor were also calculated and this study has revealed that the iron oxide concentration is a determining factor for high quality ferrites. Finally, this study shows that high permeability values of Ni-Zn and Mg-Zn ferrites occur in the cation-deficient region with x = 0.002-0.006 weight percent.